2015
DOI: 10.1145/2805789.2805796
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned From Using the RIPE Atlas Platform for Measurement Research

Abstract: We reflect upon our experience in using the RIPE Atlas platform for measurement-based research. We show how in addition to credits, control checks using rate limits are in place to ensure that the platform does not get overloaded with measurements. We show how the Autonomous System (AS)-based distribution of RIPE Atlas probes is heavily skewed which limits possibilities of measurements sourced from a specific origin-AS. We discuss the significance of probe calibration and how we leverage it to identify load is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 5 publications
0
36
0
Order By: Relevance
“…Countries with fewer probes tend to show worse latency than those we show, but we wish to exclude outliers. We do not know the local network of each VP, and it would be unfeasible to treat each probe individually, so we do not account for poor "last-mile" connections [4]. Figure 12 shows the latency for all the countries with at least 5 probes.…”
Section: Who Sees Poor Latency?mentioning
confidence: 99%
“…Countries with fewer probes tend to show worse latency than those we show, but we wish to exclude outliers. We do not know the local network of each VP, and it would be unfeasible to treat each probe individually, so we do not account for poor "last-mile" connections [4]. Figure 12 shows the latency for all the countries with at least 5 probes.…”
Section: Who Sees Poor Latency?mentioning
confidence: 99%
“…In [BES15], Bajpai et al showed that RTTs from v1 and v2 probes to the first hop router are consistently higher than for v3 probes. They do not however study the relation between the measured delays and the load of the probes.…”
Section: Lanmentioning
confidence: 99%
“…is makes it impossible for a reviewer to check for reproducibility of a submi ed work because the authors cannot reveal or may even have to obfuscate artifacts (see [1] for a formal de nition) at review time to allow double-blinding reviewing. Furthermore, datasets cannot be properly understood and appreciated without the metadata [3] that describes them which o en tends to break anonymity. e time invested in obfuscating the paper for a double-blinded submission can instead be used to prepare artifacts for reproducibility and to improve science.…”
Section: Double-blind Review Requires Obfuscationmentioning
confidence: 99%